Dimensionamento de enfermeiros para assistência em diálise peritoneal - Vieira, Kamyla Lameira (2015)
Objective : To evaluate workload of nurses in a Peritoneal Dialysis (PD) program based on the activities and time spent to perform them.Method : Qualitative design (focus group) in the first phase and quantitative in the second stage. From the list of activities of care derived from the focus group, an instrument was created and the time spent for each activity measured for 4 months. The average time for each task was multiplied by the number of occurrences of the same in the month in hours, reflecting the monthly time in hours that nurses use to perform each activity.Results : The estimation was of 495,25 of days to care for 47 patients. with a avarege of 10 days per patients. Considering number of patients (47) and 10 days for each an optimal ratio is one nurse for 23,45 patients . The most frequent nursing care activity was to assist patients during hospitalization (137,15 days), management and supervision of other health professionals, in education participating in scientific meetings and in research activities.Conclusion : We could list the nursing activities for a peritoneal dialysis nurse and suggest an easy formula to evaluate workload of nurses in PD in order to improve outcomes for patients.